2014
DOI: 10.1051/0004-6361/201423449
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic observations of the effects of a halo CME on the solar coronal structure

Abstract: We investigated the substantial restructuring of the outer solar corona in the aftermath of the halo CME that occurred on 9 March 2012. To perform our analysis, we used SOHO/LASCO, STEREO/COR1 and SDO/AIA data, which provide observations from different viewpoints. In particular, we applied the polarization ratio technique to the COR1 calibrated images to derive the three-dimensional structure of the CME and determine its direction and speed of propagation. We also estimated the CME mass from a sequence of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We also performed the 3D reconstructions with the polarization ratio technique (first described by (Moran & Davila 2004)) that has been applied by many different authors to reconstruct solar eruptions in 3D based on single viewpoint observations. This technique is particularly interesting for halo CMEs (e.g., Dolei et al 2014;Lu et al 2017), and results from this technique were compared and validated with multiple viewpoint observations (see, e.g., Mierla et al 2010Mierla et al , 2011Feng et al 2013) and also with spectroscopic observations (Susino et al 2014). Nevertheless, before Metis, all the coronagraphic space-based data so far were acquired in the VL and using only three different angular orientations of the linear polarizer, typically separated by 60 • or 120 • .…”
Section: Reconstruction With Polarization Ratiomentioning
confidence: 99%
“…We also performed the 3D reconstructions with the polarization ratio technique (first described by (Moran & Davila 2004)) that has been applied by many different authors to reconstruct solar eruptions in 3D based on single viewpoint observations. This technique is particularly interesting for halo CMEs (e.g., Dolei et al 2014;Lu et al 2017), and results from this technique were compared and validated with multiple viewpoint observations (see, e.g., Mierla et al 2010Mierla et al , 2011Feng et al 2013) and also with spectroscopic observations (Susino et al 2014). Nevertheless, before Metis, all the coronagraphic space-based data so far were acquired in the VL and using only three different angular orientations of the linear polarizer, typically separated by 60 • or 120 • .…”
Section: Reconstruction With Polarization Ratiomentioning
confidence: 99%
“…(1), we need to determine the streamer extent along the LOS. We were able to evaluate this length scale for the first time by using the information on the electron density, again, and developing a method similar to the one discussed by Dolei et al (2014b). We used the routine calc_cme_mass.pro available in the SolarSoftware library, which calculates the number of electrons providing the intensity in each pixel of the LASCO C2 pB images.…”
Section: Physical Parameter Estimatementioning
confidence: 99%
“…Apart from radio observations above active regions, another path towards coronal polarimetry has been pursued with ground-based infrared (IR) observations measuring the Zeeman effect (Lin, Penn, and Tomczyk, 2000;Tomczyk et al, 2008). Another possibility has been opened with eclipse polarization measurements in red and green channels by Kim et al (2013b) from which these authors concluded that "the polarization excess (green-red) can be explained by the presence of neutral hydrogen in the corona" (see also Dolei et al, 2014). As mentioned by Kim et al (2013b), Poland and Munro (1976) and Mierla et al (2011) had already concluded that Hα contributed to coronagraphic images of transients and coronal mass ejections (CMEs), respectively.…”
Section: Introductionmentioning
confidence: 99%